2021
DOI: 10.3889/oamjms.2021.5788
|View full text |Cite
|
Sign up to set email alerts
|

Self-confidence of Nurses Philosophy: A Concept Analysis

Abstract: BACKGROUND: The philosophical and theoretical values of nursing moved away from a systematic review of the science of nursing and experienced a shift based on paradigms. The results may be interpreted by several nursing theorists in different ways. AIM: This paper aims to analyze the development of a more comprehensive understanding toward the meaning of confidence concept of the nurses and stimulated services health, person, environment and nursing resolutions based on nursing discussions, and nursing-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
2
2
0
1
Order By: Relevance
“…Their background is one of the factors that cause a lack of confidence while on duty in the covid-19 ICU room. This study's theme results align with the literature, which states that one factor that influences a person's self-confidence is repeated experiences that strengthen beliefs about success and failure (Huffman C, 2014at Suandika, 2021.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Their background is one of the factors that cause a lack of confidence while on duty in the covid-19 ICU room. This study's theme results align with the literature, which states that one factor that influences a person's self-confidence is repeated experiences that strengthen beliefs about success and failure (Huffman C, 2014at Suandika, 2021.…”
Section: Resultssupporting
confidence: 86%
“…Participants revealed that they were more confident in performing actions after they received training. This situation is in line with the literature, which states that repeated experiences strengthen beliefs about success and failure (Huffman C, 2014in Suandika, 2021 "Ya dari kitanya sendiri ya tidak berpergian yang menguras fisik selain bekerja, istirahat cukup, jalan atau jogging." (P9) h. Sub-theme 8 is "Performing the most difficult nursing actions when caring for patients".…”
Section: Resultssupporting
confidence: 85%
“…The current study explored nurses' professional obligations when dealing with COVID‐19 patients during the pandemic. Nursing professional obligations embody nurses' ethics, values and motivations to give excellence in care for the patients (Ghazanfari et al, 2022 ; Suandika et al, 2021 ). It aids nurses in understanding professional objectives and nursing principles (McNett et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, la investigación permitió corroborar cómo esa intervención psicológica oportuna en el personal de enfermería, contribuyó muy positivamente en brindar una atención mucho más especializada al paciente COVID-19, estableciendo una relación enfermero/paciente mucho mejor consolidada en beneficio directo a la remisión de la enfermedad, contribuyendo en la elección de estrategias de afrontamiento más efectivas para cada paciente y en beneficio directo de su bienestar psicológico. Las obligaciones profesionales de enfermería encarnan la ética, los valores y las motivaciones de los enfermeros para brindar excelencia en la atención a los pacientes (Ghazanfari et al, 2022;Suandika et al, 2021). Esto ayuda a estos trabajadores de la salud, a comprender los objetivos profesionales y los principios de enfermería (McNett et al, 2021).…”
Section: Discussionunclassified